Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1097/ogx.0000000000000166
|View full text |Cite
|
Sign up to set email alerts
|

Global Women’s Health Is More Than Maternal Health

Abstract: Women's health care efforts in low-resource settings are often focused primarily on prenatal and obstetric care. However, women all over the world experience significant morbidity and mortality related to cervical cancer, sexually transmitted infections, and urogynecologic conditions as well as gynecologic care provision including insufficient and ineffective family planning services. Health care providers with an interest in clinical care in low-resource settings should be aware of the scope of the burden of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Millions of women worldwide would prefer to avoid becoming pregnant either right away or never get pregnant, but are not using any contraception 4 , 5 . Unintended pregnancy related to unmet need is a worldwide problem that affects women and their families and societies at large 2 , 6 . The concept of unmet need indicates the gap between some women's reproductive intentions and their contraceptive behavior for Family Planning (FP) 3 , 4 , 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Millions of women worldwide would prefer to avoid becoming pregnant either right away or never get pregnant, but are not using any contraception 4 , 5 . Unintended pregnancy related to unmet need is a worldwide problem that affects women and their families and societies at large 2 , 6 . The concept of unmet need indicates the gap between some women's reproductive intentions and their contraceptive behavior for Family Planning (FP) 3 , 4 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Butajira on determinants of low family planning use showed that unmet need of contraception was 52.4% of which 74.8% was attributed to spacing and the rest for limiting 8 . A study conducted in Misha-Southern Ethiopia and Dangila-Amhara region revealed that 26.5% 13 and 17.4 % 2 of married women had unmet need for family planning.…”
Section: Introductionmentioning
confidence: 99%